Pengaruh resin resol pada pembuatan film akrilat dengan menggunakan sinar ultraviolet - Dwi Wahini Nurhajati (Majalah Kulit, Karet, dan Plastik, 1989)
The aim of this research to investigate photoinitioting ability of resole resin in photocrosslinking of acrylate monomers. In this article, compounds consist of acrylate monomers. In this article, compounds consist of acrylate monomers (ECA and DPCA 60) and resole resin were irradiated with ultraviolet light (120 watt/cm) for 3 times and then analised. Compounds with high resole resin and DPCA – 60 content formed insoluble transparent thin film. It was found that resole resin played an important role in the formation of polymer crosslinked structures in acrylate monomers. However, the value of the insoluble thin film fraction did not greater than 40,16% at present. The highest film fraction was obtained from a compound with resole resin 40 wt. % and DPCA 60 = 60 wt. % content.